2001
DOI: 10.1051/0004-6361:20010885
|View full text |Cite
|
Sign up to set email alerts
|

NGC 3310, a galaxy merger?

Abstract: Abstract. The H i structure and kinematics of the peculiar starburst galaxy NGC 3310 (Arp 217, UGC 5786) are discussed. New evidence bearing on the origin of the starburst is presented. The bulk of H i coincides with the bright optical disk and shows differential rotation. Its velocity dispersion is, however, unusually large for a spiral galaxy (up to 40 km s −1 ), suggesting that the disk is highly perturbed as already indicated by optical emission line spectroscopy. There are, in addition, two prominent H i … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 17 publications
(34 reference statements)
3
63
0
Order By: Relevance
“…The inner shell features have blue colors, H p 72 0 indicative of recent star formation. They also lie within the main H i disk of NGC 3310 (Kregel & Sancisi 2001) and are centered on the galaxy. These features are likely to be associated with NGC 3310's disk.…”
Section: Photometrymentioning
confidence: 95%
See 4 more Smart Citations
“…The inner shell features have blue colors, H p 72 0 indicative of recent star formation. They also lie within the main H i disk of NGC 3310 (Kregel & Sancisi 2001) and are centered on the galaxy. These features are likely to be associated with NGC 3310's disk.…”
Section: Photometrymentioning
confidence: 95%
“…It has been previously suggested that NGC 3310 collided with either a small dwarf galaxy (Balick & Heckman 1981;Schweizer & Seitzer 1988) or possibly a larger, more gas-rich galaxy (Kregel & Sancisi 2001), while the H i tidal tails mapped by Kregel & Sancisi (2001) imply that NGC 3310 may be the result of an equal mass merger. They point out that the existence of a disk in the postmerger system implies either that disks are more resilient than previously thought or that we may be seeing a disk that was formed as a result of this collision.…”
mentioning
confidence: 99%
See 3 more Smart Citations